Future of the Balkans in the Time of Integration and Globalization – Dangers and Challenges of Contemporary Times - Sulejmani, Rizvan; GJurovski, Marjan (Konrad Adenauer Foundation, Republic of North Macedonia Institute for Democracy “Societas Civilis”, Skopje, 2021)
A number of authors have written on the topic of divisions between the East and the West, or respectively, the Orient vs Occident, presenting such divisions as if they are mainly taking place between two systems of values. These divisions are cultural, and even more religious and historical. The most vocal proponent of such divisions is Edward W. Said who says that the Orient is the spirit which has been created by the Occidentalist, and this division is grounded on the way of thinking along ontological and epistemological differences1. Kulenovic, by recalling Preston, suggests that the idea of superiority of the western man has not been born all of a sudden. The idea of superiority and supremacy of the colonial man has its own evolution. In his view, during the early period of trade exchanges between European and other non-European peoples, the Muslims were observed as exotic, but culturally equal. During the renaissance period, as the trade further expanded, the non-Europeans began to stand for innocence, therefore the term the wild noblemen. As colonialism was spreading during the nineteenth century, so the perception of them being wild and uncivilized started to equally change2 . John M. Hobson, on the other hand, maintains that the divisions between the East and the West gained momentum after the fall of Constantinople to the Ottomans in 1453. To support this claim, he points to the cylindrical map projected by the geographer Gerardus Mercator in 1569 in which there is an obvious unequal representation, given that the southern hemisphere is twice the size of the northern one, while the map shows quite the opposite, two-thirds covering the northern as opposed to the one-third covering the southern hemisphere3. Our interest, however, in none of analyzing the divisions between the East and the West, but rather of scrutinizing the position of the Balkans, which geographically is spreading along these imaginary division lines. To this end, we shall refer to the observations made by Maria Todorova, who presents her views in her book „Imaging the Balkans”.
Keywords: Balkans’ place, borders, globalization, integration